1972
DOI: 10.1107/s0567740872007848
|View full text |Cite
|
Sign up to set email alerts
|

Structures de complexes π carbonyés du fer. II. Structure cristalline et moléculaire de l'aldéhyde cinnamique fertricarbonyle: C6H5CH=CH–CHO.Fe(CO)3

Abstract: The crystal structure of tricarbonyl(cinnamaldehyde)iron, C6HsCH=CH-CHO.Fe(CO)3, has been determined using molybdenum K~ radiation and counter techniques. Crystals are monoclinic with a= 9.723+0.010, b--7.116 + 0-007, c= 18.938_+0.018 A; fl= 115.05+0.15°; Z=4; space group P21/c. The tricarbonyl(cinnamaldehyde)iron must be considered as a zr complex. The two oxygen lone pairs do not play a part in the bonding with the metal and the structure is similar to that found in tricarbonyl-(Ncinnamylideneaniline)iron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…By comparing the M-CO bond lengths in 7, 10, and 14, we have tried to give an absolute assignment to the CO resonances. As already described for similar complexes [30] [32], we have also found that in these compounds the M-CO bonds are longer in the case of the CO cis to the 0x0 group. Howell et al [30] attributed this behavior to a smaller n-back-donation and assigned the up-field signals to the CO cis to the 0x0 group (6(C(ll)) < 6(C(12)), see Figs.…”
Section: ] (10)supporting
confidence: 87%
“…By comparing the M-CO bond lengths in 7, 10, and 14, we have tried to give an absolute assignment to the CO resonances. As already described for similar complexes [30] [32], we have also found that in these compounds the M-CO bonds are longer in the case of the CO cis to the 0x0 group. Howell et al [30] attributed this behavior to a smaller n-back-donation and assigned the up-field signals to the CO cis to the 0x0 group (6(C(ll)) < 6(C(12)), see Figs.…”
Section: ] (10)supporting
confidence: 87%
“…The C–C and C–O distances of the C4–C5–C6-O1 fragment display enhanced delocalization versus the free α,β-unsaturated ketone. This pattern is consistent with that observed in other η 4 -(α,β-unsaturated ketone)-iron(0) complexes, e.g., [(η 4 -PhCHCHCHO)­Fe­(CO) 3 ] and [(η 4 -PhCHCHCHO)­Fe­(CO) 2 (PPh 3 )] . In the structure of 5 , the indenimine ligand is bonded with the iron center via the C5–C6–C7–C8 fragment.…”
Section: Results and Discussionmentioning
confidence: 81%
“…A study of the dependence of the g 2 versus g 1 coordination on the metal and ligand nature appeared recently [17]. Depending on the number of ligands, the coordination can change from g 2 CC to g 4 [18][19][20]. In rare cases the g 2 CO coordination has been found with Re and Os complexes [21,22].…”
Section: Introductionmentioning
confidence: 97%